Primer Comando Capital, telecriminology and the criminal sub-records:: Main challenges of publi security management in Paraguay, from 2018 to 2023 (Legal journal - Research in Legal and Social Sciences, 2020)
The candidates for President, and the Presidents elected in the last years, from the various political parties and ideological orientations, have shared a campaign promise, namely to improve national security, this topic also occupies a great place in public debate, in decision-makers and in the media, however, the scientific output that adds information on the dimensions of the phenomenon and its main characteristics, is still little, given the fact that the approach of the topic, prioritizes perception-based decisions, over empirical evidence. This might be the reason why 97% of the population thinks that delinquency rose, while homicides decreased by 40% between 2010 and 2018. In this context, the present article reflects on the main challenges of public security management for the five-year term 2018-2023, taking as starting points the presentation and analysis of objective information provided by the National Police, the results of the National Victimization Survey 2017, and the fieldwork conducted in the border area with Brazil. The findings indicate the need to move towards a drafting and implementation of a security policy, that procures the reduction of crime, and the fear of it, a policy that encourages the crime report, and enables effective communication channels of institutional management concerning the fight against crime, the mentioned findings also indicate the need to a multidisciplinary, interinstitutional and professional approach of the fight against transnational organized crime, that profits from the institutional wickness of our country, and sees in that wickness the opportunity for anchoring and expansion. The criminal organization of largest presence and fastest growth is the Primer Comando Capital, PCC onwards
Keywords: security policy; organized crime; Primer Comando Capital; telecriminology; criminal sub-record